Magnetic Organization of Neural Networks via Micro‐Patterned Devices. Issue 19 (12th August 2020) - Marcus, Michal; Indech, Ganit; Vardi, Naor; Levy, Itay; Smith, Alexandra; Margel, Shlomo; Shefi, Orit; Sharoni, Amos
Abstract: Guiding neuronal migration and outgrowth has great importance for therapeutic applications and for bioelectronics interfaces. Many efforts have been devoted to the development of tools to form predesigned structured neuronal networks. Here, a unique approach to localize cell bodies and direct neurite outgrowth is described based on local magnetic manipulations. Inspired by spintronic devices, a multi‐layer deposition process is developed to generate nanometric‐thick films with perpendicular magnetization that provide stable attraction forces toward the entire magnetic pads. PC12 cells, a common neuronal model, are transformed to magnetic units by incubation with superparamagnetic nanoparticles, which are then plated and differentiated atop the substrates. The vast majority of MNPs‐loaded cells adhere to the magnetic pads, showing high affinity to the magnetic patterns in correlation with numerical simulations of the magnetic force strength. Additionally, neuronal growth analysis shows that the magnetic substrate is effective in directing the extending neurites, which tend to remain atop the magnetic pads, and even follow complex patterns such as hexagons. This suggests that the MNPs diffuse into the neuronal processes throughout network formation. The ability to remotely control neuronal motility together with network design via smart magnetic materials opens possibilities for new neuronal interfaces and implantable therapeutic devices. Abstract : A unique approach to control neural network formation magnetically is developed. Inspired by spintronics devices, chips with nanometer‐thick magnetic pads are generated. PC12 cells, transformed into magnetic units by superparamagnetic nanoparticle absorption and plated on the chips, show high affinity to the pads even to complex patterns. Smart magnetics to remotely control neuronal motility open possibilities for new interfacing implants.